2020
DOI: 10.1183/13993003.03028-2020
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis prevention in children: a prospective community-based study in South Africa

Abstract: Tuberculosis preventive therapy reduces tuberculosis risk in children. However, the effectiveness of tuberculosis preventive therapy in children living in high burden settings is unclear.In a prospective observational community-based cohort study in Cape Town, South Africa, we assessed the effectiveness of routine tuberculosis preventive therapy in children ≤15 years of age in a tuberculosis and HIV high-prevalence setting.Among 966 children (median age 5.07 years; inter-quartile range [IQR] 2.52,8.72), 676 (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Approximately 1 million children develop tuberculosis disease each year globally, half occurring in early childhood. 1 , 2 The risk of tuberculosis disease after recent exposure is greatest before age 5 years, 3 , 4 , 5 , 6 approaching 20% at 2 years postinfection. 3 These high progression rates have been ascribed to an immature immune system in early life; however, the mechanisms are not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 1 million children develop tuberculosis disease each year globally, half occurring in early childhood. 1 , 2 The risk of tuberculosis disease after recent exposure is greatest before age 5 years, 3 , 4 , 5 , 6 approaching 20% at 2 years postinfection. 3 These high progression rates have been ascribed to an immature immune system in early life; however, the mechanisms are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, tuberculosis disease and cytomegalovirus have similar age distributions with the greatest risk in infancy and adolescence. 3 , 4 , 5 , 6 , 9 , 14 A case–control study found that children with tuberculosis disease had higher concentrations of cytomegalovirus-specific IFN-γ responses. 15 Large, population-based, prospective, cohort studies from high-burden settings such as sub-Saharan Africa with serial follow-up testing of cytomegalovirus and tuberculosis disease in infants and young children are not available, but they are needed to further understand the pathogenesis and temporal dynamics between these two hyperendemic pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The high disease risk in young children with recent TB exposure provides urgency to give TPT and decreases the number needed to treat to prevent one case of TB (Anon, 2021f;Mandalakas et al, 2020). TPT is also extremely well tolerated in young children and given the pauci-bacillary nature of their disease there is minimal risk of inducing drug resistance, even if disease is missed by symptom-based screening.…”
Section: Closing the Tb Prevention Gapmentioning
confidence: 99%
“…There is a common misperception that there is a need to document TB infection by performing a tuberculin skin test (TST) or interferon gamma release assay (IGRA) prior to initiating TPT. While these tests have value in establishing TB infection in individuals who may benefit from TPT (Mandalakas et al, 2020), their added value in close contacts of an infectious TB case is limited, especially in high incidence settings where rates of past TB infection are high. Their added value is also less clear in vulnerable young contacts in whom careful consideration should be given to sensitivity concerns and the post exposure 'conversion window'.…”
Section: Closing the Tb Prevention Gapmentioning
confidence: 99%
“…The first line of solid evidence was presented in a series of studies documenting remote transmission from humans to guinea pigs (1), followed by reports of human-to-human airborne transmission in closed environments, such as ships (2). More recently, household contact studies have provided valuable evidence regarding transmission dynamics (3)(4)(5). Nevertheless, there is now substantial evidence that most transmission occurs outside the household (6,7).…”
mentioning
confidence: 99%